Elevation of serum oxidative stress in patients with retina vein occlusions. Issue 2 (26th September 2018) - Chen, Kuan‐Hsuan; Hsiang, En‐Lin; Hsu, Min‐Yen; Chou, Yueh‐Ching; Lin, Tai‐Chi; Chang, Yuh‐Lih; Tsai, Ching‐Yao; Li, Tzu‐Hsuan; Woung, Lin‐Chung; Chen, Shih‐Jen; Peng, Chi‐Hsien; Hwang, De‐Kuang
Abstract: Purpose: Retina vein occlusion (RVO) is a visual‐threatening retinal disease that causes irreversible impaired quality of life. The contribution of oxidative stress behind clinical course of RVO was rarely investigated. The study aimed to measure the serum oxidative biomarker in patients with RVO to investigate further physical response. Methods: We measured the serum levels of malondialdehyde (MDA), 8‐hydroxy‐2‐deoxyguanosine (8OHdG), Sirutin 1 (SIRT1), peroxisome proliferator‐ activated receptor gamma (PPAR‐r), Peroxisome proliferator‐activated receptor gamma coactivator 1‐alpha (PGC‐1 α ), orkhead box protein O1 (FOXO1), orkhead box protein O3 (FOXO3), catalase, (SOD) and hydrogen peroxide (H2 O2 ) among 19 patients with cataract as control group and 36 patients with RVO, respectively. Results: The mean MDA, 8OHdG and hydrogen peroxide in the serum were significantly higher in patients with RVO compared with the results in control group subjects. Whereas SIRT1, PPAR‐r, PGC‐1, FOXO1, FOXO3, catalase and SOD levels in serum were significantly decreased in patients with RVO compared with control group. Conclusion: We demonstrated that the serum level of MDA, 8OHdG and hydrogen peroxide is increased in patients with RVO. Among these, the elevation of MDA, 8OHdG and hydrogen peroxide suggests the increasing of serum oxidative stress in RVO patients. All enzymes related reactive oxygen species scavenge were decreased. Thus, focal RVO may increase systemic oxidative stress within serum.